ANALISIS KEBUTUHAN PENGEMBANGAN BUKU AJAR ENGLISH FOR MATHEMATICS - Ratih Ayu Apsari; Sariyasa; Nourma Pramestie Wulandari; Tabita Wahyu Triutami (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
English for Mathematics (EFM) is one of the important courses to prepare the prospective mathematics teacher in teaching mathematics using English as language of instruction. Besides that, EFM also enable the students in mathematics education department to employ more references as learning sources. Reflected to the important of students’ ability in EFM, we plan to develop the textbook related to the course. The whole study will use the method of Research & Development with three steps of Preliminary Research, Prototyping Stage dan Assessment Phase. The present study was focused on the first stage to analysis the needs of the textbook development. The subjects were 27 students of second year mathematics education study program in a state university in Nusa Tenggara Barat, Indonesia. The subjects were experienced the course of EFM in previous year. The data were gathered from students’ written work and interview with students and lecturers of EFM. We analyzed the data using quantitative descriptive method to evaluate the students’ mastery in EFM. From the analysis, it was found that the students’ score were lacking in mathematical terms and spoken language of mathematical symbols. The interview with the lecturers also confirmed that the learning sources in EFM is still limited. Therefore, to support the students in learning EFM better, the textbook is highly needed.